Role of Hyperbaric Oxygen Therapy in Traumatic Brain Injury—Evidence-Based Consensus - Velho, Vernon; Kharosekar, Hrushikesh; Bhople, Laxmikant; Palande, Deepak A. (Indian Journal of Neurotrauma, 2020)
Traumatic brain injury (TBI) is a major health problem in India and worldwide, resulting in significant morbidity, mortality, and disabilities of young and productive group of society. Various treatment modalities in the immediate period following a TBI are focused on altering the acute pathophysiology. Secondary injury is precipitated by ischemia resulting from decreased cerebral blood flow leading to hypoxia and is particularly likely to occur in the first 24 hours after injury. Hyperbaric oxygen therapy (HBOT) targets TBI-induced ischemia by exposing patients to an environment that substantially increases the amount of O2 inspiration (100% O2 at >1 atmosphere absolute), producing an increased O2 concentration in the plasma and thus increased delivery of O2 for diffusion to brain tissue. Despite the capacity of HBOT to protect against secondary ischemic damage, the use of HBOT for the treatment of TBI has been controversial. To gain acceptance in routine clinical use, a clinical method of assessing its effectiveness in the individual patient, computed tomography perfusion scan, single-photon emission computed tomography scans, and other intermediate indicators of the effects of HBOT should be examined by large and high-quality studies.
Keywords: hyperbaric oxygen therapy; traumatic brain injury